Does Research Mobility Have an Effect on Productivity and Impact? - Halevi, Gali; Moed, Henk F.; Bar-Ilan, Judit (International Higher Education, 2016)
This article examines whether domestic or international mobility of scientists have positive effect on the productivity or impact of their work. We analyzed 100 top producing authors from 7 disciplines and found that mobility between at least two affiliations increases both output (number of publications) and impact (number of citations). However, mobility between countries does not seem to have a positive impact as domestic affiliation mobility.